2016
DOI: 10.1002/ajim.22658
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in precarious workers’ health care access in South Korea

Abstract: We found that precarious workers had more difficulty accessing health care or receiving health checkups or cancer screenings than their non-precarious counterparts. Am. J. Ind. Med. 59:1136-1144, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…A person can be directly employed, employed through an agency or self-employed as well as being employed in other indirect ways depending on context. In the quantitative studies, being employed through an agency or being self-employed was usually contrasted to being directly employed (23,27,28,31,34,49,51,57). From the analysis of the qualitative definitions, it was possible to capture the negative connotations associated with some of these subthemes, although no explicit comparison was made.…”
Section: Included Dimensionsmentioning
confidence: 99%
“…A person can be directly employed, employed through an agency or self-employed as well as being employed in other indirect ways depending on context. In the quantitative studies, being employed through an agency or being self-employed was usually contrasted to being directly employed (23,27,28,31,34,49,51,57). From the analysis of the qualitative definitions, it was possible to capture the negative connotations associated with some of these subthemes, although no explicit comparison was made.…”
Section: Included Dimensionsmentioning
confidence: 99%
“…Another issue in Theme 3 is the employment status of affected workers. Workers’ employment status affects health and causes safety disparities, which is exacerbated by unregulated and unsafe workplaces [ 23 - 25 ]. International reviews have found that occupational injury rates for nonstandard and temporary workers are greater than those for permanent workers [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, self-employed individuals account for more than 30% of the labor market [28], of which 80% are self-employed insurance beneficiaries [8]. Previous studies demonstrate that precarious employment conditions with lower purchasing power and job insecurity result in poor health status or outcomes; moreover, such workers generally experience significant barriers to medical care access [29][30][31]. Recently, Choi et al clearly verified that self-employed status, defined as workers who manage their own businesses or carry out professional matters under their own responsibility, affects unmet dental care needs [24].…”
Section: Discussionmentioning
confidence: 99%